1999
DOI: 10.1038/sj.bjc.6690115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 10q23 chromosomal region and the PTEN gene in human sporadic breast carcinoma

Abstract: SummaryWe examined a panel of sporadic breast carcinomas for loss of heterozygosity (LOH) in a 10-cM interval on chromosome 10 known to encompass the PTEN gene. We detected allele loss in 27 of 70 breast tumour DNAs. Fifteen of these showed loss limited to a subregion of the area studied. The most commonly deleted region was flanked by D10S215 and D10S541 and encompasses the PTEN locus. We used a combination of denaturing gradient gel electrophoresis and single-strand conformation polymorphism analyses to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 38 publications
1
69
1
1
Order By: Relevance
“…Detailed genotyping studies have demonstrated that structural alterations in PTEN are rarely observed. 9,17,19,21 Loss of heterozygosity (LOH) in 10q23 however, is reported in up to 1 ⁄3 of such breast cancers, 16 -19 associated with adverse pathologic features. 16,18 Alternative mechanisms that have been suggested include silencing of the PTEN promoter through hypermethylation, 51,53,54 increased degradation, 9 or haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed genotyping studies have demonstrated that structural alterations in PTEN are rarely observed. 9,17,19,21 Loss of heterozygosity (LOH) in 10q23 however, is reported in up to 1 ⁄3 of such breast cancers, 16 -19 associated with adverse pathologic features. 16,18 Alternative mechanisms that have been suggested include silencing of the PTEN promoter through hypermethylation, 51,53,54 increased degradation, 9 or haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Activating mutations in PI3K subunit genes PIK3CA and PIK3R1, and inactivating mutations in PTEN are common in a wide variety of malignancies, including colon, breast, liver, ovarian, leukemia, brain tumors, melanoma, prostate, thyroid, and lymphoma. [38][39][40][41] Gain of function mutations in all three AKT genes have been identified in adult malignancies, including breast, colon, melanoma, and ovarian. [7,[42][43][44] No mutations have been identified in any AKT isoform in childhood cancer; however, chromosomal gains amplifying the AKT1 gene have been described recently in rare cases of childhood AML, T-cell ALL, and gliosarcoma.…”
Section: Pi3k/akt/mtor Signaling In Cancermentioning
confidence: 99%
“…This disease, which is also known as multiple hamartoma syndrome, is another familial syndrome that includes many different types of cancer conditions including early onset breast cancer. Mutations have been reported to occur at PTEN in breast cancer in varying frequencies (5-21%) (Rhei et al, 1997, Singh et al, 1998, Feilotter et al, 1999, DeGraffenried et al, 2004, Hollestelle et al, 2007. Loss of heterozygosity (LOH) at PTEN is probably more common (30%) (Singh et al, 1998).…”
Section: Signaling Pathways and Breast Cancermentioning
confidence: 99%